Патогенез метаболічного синдрому та його зв'язок із перебігом доброякісної гіперплазії передміхурової залози - Кирилюк, М. Л.; Костєв, Ф. І.; Черпак, Б. Д.; Шаталюк, С. С. (Clinical Endocrinology and Endocrine Surgery, 2012)
The data of concerning the classification of the metabolic syndrome and its clusters in relation to the pathogenesis of benign prostates hyperplasia are presents in the review.